Potential of the flora of Peru emphasizing in the Asteraceae family against Trypanosoma cruzi - Delgado-Paredes, Guillermo E.; Delgado Rojas, Paulo R.; Rojas Idrogo, Consuelo (Revista Cubana de Medicina Tropical, 2024)
Introduction: American trypanosomiasis or Chagas diseases, caused by Trypanosoma cruzi and Human African trypanosomiasis, caused by Trypanosoma brucei, are two neglected tropical, endemic and fatal disease, that affect 20 million people and cause 95,000 deaths per year in tropical and subtropical areas of the world. Objective: The objective of this review was to show the potential of the flora of Peru, emphasizing the Asteraceae family, against Trypanosoma cruzi, comparing it with American genera and species studied in various countries. Methods: A review of scientific articles on the subject was carried out, especially taken from the Scopus, SciELO, ScienceDirect, Medline and PubMed databases of American plant species, covering a period of twelve years (2010 to 2022). Results: A wide list of genera and species of the Asteraceae family and the flora of Peru with great potential in the treatment of trypanosomiasis is presented. Most of these species belong to the families Asteraceae, Piperaceae, Annonaceae, and Lauraceae. In the Asteraceae family, 48 genera and 76 species with trypanocidal activity were recorded, corresponding to 29 genera and 57 species for the flora of Peru. In these 29 genera, 174 endemic species potentially useful in the treatment of T. cruzi have been reported. Conclusions: The flora of Peru has around 22,000 species. Some of these genera and species are found in the flora of various American countries and have been tested in the treatment of Chagas disease, so the flora of Peru offers new opportunities in its treatment.